Basedow på dansk. En 200-årig misforståelse i pædagogikkens historie - Fink-Jensen, Morten (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
The educational ideas of the Enlightenment gained marked acceptance in Denmark towards the end of the 18th century in the form of the so-called philanthropic movement. The dominant figure in this movement was the German educational theorist Johann Bernhard Basedow (1724–90), and since the 19th century it has been generally believed that Basedow’s book entitled Effective guidelines for the optimal education of children was a telling expression of the movement’s influence in Denmark. This work has in reality nothing to do with Basedow, but is rather a translation of a 17th century French educational handbook. Contrary to what has hitherto been believed, a Danish translation of Baselow could not therefore be helpful in raising interest in philanthropism.